Interleukin-33 in Malignancies: Friends or Foes? - Shen, Jia-Xin; Liu, Jing; Zhang, Guo-Jun (Frontiers in Immunology, 2018)
The human Interleukin-33 (IL-33), a member of the IL-1 family, is the cytokine as a cell endogenous alarmin, released by damaged or necrotic barrier cells (endothelial and epithelial cells). The signal transduction of IL-33 relies on recognition and interaction with specific receptor ST2, mainly expressed in immune cells. In both innate and adoptive immunity, IL-33 regulates the homeostasis in response to stress from within/out the microenvironment. Various, even negative biofunctions of IL-33 pathways have now been widely verified in pathogenesis among immunological mechanisms, like Th2-related immune-stimuli, inflammation/infection-induced tissue protectors. A larger versatility in studies of IL-33 on malignancies now focuses on: 1) promoting myeloid-derived suppressor cells (MDSC), 2) intervention towards CD8+ T, Natural Killer (NK) cell infiltration, group 2 innate lymphoid cells (ILC2) proliferation, dendritic cells (DC) activation, and 3) inhibiting tumor growth and/or further metastasis as an immunoadjuvant. Although IL-33 functioned pro-tumorigenically in various cancers, for some cancer types the findings so far are controversial. This review begins from a summarized introduction of IL-33, to its remarkable implications and molecular transduction pathway in malignant neoplasms, ends with latest inspiration for IL-33 in treatment.